The One Health teaching clinic as an interprofessional education learning environment: an Austrian community case study of veterinary PhD students' competency development through co-design with pre-service science teachers - Ulrich Hobusch; Sascha Krebser; Franziska Messenböck; Sebastian Linnartz; Veronika Fraisl; Eva-Maria Bartl; Damien Ernst; Pia Maria Saria; Kristina Schmidhofer; Simona Winkler; Christine Aurich; Martin Scheuch (Frontiers in Veterinary Science, 2026)
One Health education increasingly requires competencies that conventional veterinary doctoral training does not systematically cultivate, including science communication with non-scientific audiences, transdisciplinary collaboration, and the ability to translate specialized research into societal and educational contexts. This community case study examines how five veterinary PhD students at the University of Veterinary Medicine Vienna experienced the One Health Teaching Clinic (OHTC), a 13-week interprofessional interprofessional teacher education course in which they collaborated with pre-service science teachers to develop classroom materials based on their respective One Health doctoral projects. The OHTC is structured through the Synoptic Transfer Framework, a Two-Eyed Seeing-informed pedagogical framework that organizes changing perspectives between scientific knowledge and lifeworld understanding. Qualitative content analysis of 114 segments from learning journals, a focus group, and videographic recordings used the NEOH One Health competency framework deductively, while segments beyond the framework were coded inductively. Three patterns were central. First, the OHTC surfaced an unexpected language adaptation challenge: veterinary doctoral students whose research communication was strongly shaped by English-language scientific discourse struggled to translate specialized knowledge into accessible German explanations for non-specialist educational audiences. Second, seven situated communication practices emerged across all five cases, including content adaptation for specific audiences, the use of analogies and visuals, adjustment of language register between scientific and everyday discourse, balancing precision and accessibility, concrete exemplification, content prioritization, and risk communication that conveyed zoonotic risk without inducing unnecessary alarm. Third, participants began to recognize educational research as a legitimate knowledge system, describing an epistemological shift from a worldview confined to “ p -values and graphs.” Notably, 32.5% of coded material fell outside the NEOH framework. Within this beyond-NEOH material, 20 unprompted implementation proposals indicated that the co-design format activated strategic action competence not fully captured by current One Health competency models. Although the findings are exploratory and limited to a single cohort at two Austrian institutions, the study suggests that structured interprofessional co-design between veterinary researchers and education professionals can create meaningful opportunities for developing the societal engagement capacities that One Health demands.